Virtual Classroom Management in Islamic Higher Education: Optimizing Scheduling Efficiency and Academic Activities - Agus Riswandi; Rustam Lubis; Putri Syahri; Yurmaini Yurmaini (Al-Fikru: Jurnal Ilmiah, 2026)
Digital transformation encourages Islamic higher education institutions to develop more flexible, efficient, and integrated academic management systems. One form of this transformation is the implementation of virtual classroom management, which not only supports the learning process but also has the potential to optimize academic scheduling and the organization of academic activities. This study aims to analyze virtual classroom management in Islamic higher education institutions, examine its contribution to scheduling effectiveness, analyze its role in optimizing academic activities, and identify the challenges of its implementation. The study employs a descriptive qualitative approach using a library research method. Data were obtained from relevant scholarly journal articles, academic books, policy documents, and other relevant sources, which were analyzed through content and thematic analysis. The findings indicate that virtual classroom management through the integration of Learning Management Systems (LMS) and digital scheduling systems can improve academic management efficiency, reduce scheduling conflicts, accelerate information dissemination, and support the organization of learning activities. However, its effectiveness is influenced by infrastructure readiness, digital literacy, pedagogical competence, and institutional governance.